2021
DOI: 10.3389/fmicb.2021.746121
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptomic Insight of Giant Sclerotium Formation of Wood-Decay Fungi

Abstract: Many fungi form persistent and dormant sclerotia with compact hardened mycelia during unfavorable circumstances. While most of these sclerotia are small in size, Wolfiporia cocos, a wood-decay fungus, grows into giant sclerotia, which are mainly composed of polysaccharides of linear (1→3)-β-D-glucans. To explore the underlying mechanism of converting sophisticated wood polysaccharides for biosynthesis of highly homogenized glucans in W. cocos, we sequenced and assembled the genome of a cultivated W. cocos stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 66 publications
3
17
0
Order By: Relevance
“…Based on the comparison of OrthoMCL gene families and whole genomes, genetic differences were also found by Luo et al (2020) between North American (MD-104, see Floudas et al 2012) and Chinese (CGMCC5.78) strains. Similar result was obtained by Cao et al (2021), who sequenced a cultivated strain of Fuling mushroom (2018LT001), originated from Hubei, China.…”
Section: Differences Between "Fuling" and "Tuckahoe" Samplessupporting
confidence: 85%
See 1 more Smart Citation
“…Based on the comparison of OrthoMCL gene families and whole genomes, genetic differences were also found by Luo et al (2020) between North American (MD-104, see Floudas et al 2012) and Chinese (CGMCC5.78) strains. Similar result was obtained by Cao et al (2021), who sequenced a cultivated strain of Fuling mushroom (2018LT001), originated from Hubei, China.…”
Section: Differences Between "Fuling" and "Tuckahoe" Samplessupporting
confidence: 85%
“…Consequently, both traditional morphological examinations (Fries 1822;Merrill 1917), molecular phylogenetic studies based on barcoding sequences (Wu et al 2020), and genome-level comparisons (Luo et al 2020;Cao et al 2021) prove that Asian Fuling samples differs from the North Americans. So, it seems justified to treat "Fuling" (Pachyma hoelen) and Sclerotium cocos (syn.…”
Section: Differences Between "Fuling" and "Tuckahoe" Samplesmentioning
confidence: 99%
“…Notably, the genome of F. gymnauchen was large, possibly due to a higher repetitive sequence content. The repeat ratio of the genome affects not only genome size and recombination but also the chromosome’s structure [ 29 , 30 ]. If genomic heterozygosity is exorbitant, genome assembly will be difficult [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the functions of SOAT in the synthesis of pharmacologically active compounds are still largely unknown in medicinal fungi. Furthermore, although the genome [ 25 , 35 ], transcriptome [ 26 ], secretome [ 36 ], and mitochondrial genome [ 37 ] of W. cocos have been investigated, the molecular mechanisms involved in the biosynthesis of secondary metabolites remained incompletely understood. The gene function study of WcSOAT has not been reported before.…”
Section: Discussionmentioning
confidence: 99%